2020
DOI: 10.3390/microorganisms8040483
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Just Bacteria: Functional Biomes in the Gut Ecosystem Including Virome, Mycobiome, Archaeome and Helminths

Abstract: Gut microbiota refers to a complex network of microbes, which exerts a marked influence on the host’s health. It is composed of bacteria, fungi, viruses, and helminths. Bacteria, or collectively, the bacteriome, comprises a significant proportion of the well-characterized microbiome. However, the other communities referred to as ‘dark matter’ of microbiomes such as viruses (virome), fungi (mycobiome), archaea (archaeome), and helminths have not been completely elucidated. Development of new and improved metage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 155 publications
2
79
1
2
Order By: Relevance
“…The elderly gut is home to three main phyla, namely Ascomycota, Basidiomycota and Zygomycota. The most prevalent genera among the elderly Danes were Penicillium , followed by Candida , and Aspergillus (Supplementary Table 1), as previously described in preliminary studies using similar cohort [39]– [41].…”
Section: Resultsmentioning
confidence: 55%
“…The elderly gut is home to three main phyla, namely Ascomycota, Basidiomycota and Zygomycota. The most prevalent genera among the elderly Danes were Penicillium , followed by Candida , and Aspergillus (Supplementary Table 1), as previously described in preliminary studies using similar cohort [39]– [41].…”
Section: Resultsmentioning
confidence: 55%
“…A larger sample size is required for future studies to account for the high degree of inter-individual variability in the intestinal virobiota, to get a complete picture of the virome of CF patients, and minimise the influence of outliers (which is controlled for using the ANCOM analysis [49]). Although the percentage of predictions mapped to functional terms is small, a recent review of human gut virome literature identified 18 studies, none of which performed a functional annotation [50]. Bacterial contamination rates in our sequencing data were quite varied and could require optimisation, however the level is on par with other current studies [27,28].…”
Section: Discussionmentioning
confidence: 93%
“…Gut virome genes are also implicated in human metabolism, inflammation and carcinogenesis modulation [114]. Recent evidence points out to a new role of bacteriophages in liver metabolism and immune response regulation in humans [115].…”
Section: Gut Virome and Liver Diseases At The Time Of Sars-cov-2 Pandmentioning
confidence: 99%